Pengaruh Substitusi Filler Kapur Tohor Terhadap Karakteristik Marshall Campuran Aspal Concrete Binder-Course (AC-BC) - Subhan Mulyana; Sulwan Permana; Taupik Saepul Rohman (Jurnal Konstruksi, 2025)
The physical condition of roads can be improved by optimizing the performance of the asphalt mixture used. This study aims to analyze the effect of using quicklime as a filler material in AC-BC asphalt mixes. The research method used laboratory tests with variations in asphalt content of 4.5%, 5%, 5.5%, 6%, and 6.5% and variations in quicklime filler modification of 1%, 2%, 3%, 4%, and 5%. The tests included optimum asphalt content (OAC), stability, Marshall, fatigue (flow), and durability. The results showed that the optimum OAC was 6.25%, the highest stability was 1425 kg at a lime variation of 2%, the highest flow was 3.93 mm at a variation of 5%, and the best durability was 72.36% at a variation of 4%. These results meet the specifications of Bina Marga 2018 Revision 2, indicating that pure lime has the potential to be used as an alternative filler in asphalt mixtures.